Gestational diabetes: a contributor to long-term thyroid dysfunction and disease - Shih, Yu-Hsiang; Hsieh, Chia-Jung; Wang, Shao-Jing; Lu, Chien-Hsing; Tseng, Jenn-Jhy (Frontiers in Endocrinology, 2025)
BackgroundEmerging evidence links gestational diabetes mellitus (GDM) with thyroid dysfunction, but the long-term risk of clinically diagnosed thyroid diseases after GDM remains unclear.ObjectiveTo assess the long-term risk of specific thyroid disorders in women with prior GDM compared with those without GDM.MethodsWe performed a retrospective cohort study using the TriNetX U.S. Collaborative Network, including de-identified records from >80 healthcare organizations. Women aged 16–45 years with pregnancies from 2001 to 2015 were eligible; those with pre-existing hypertension, diabetes, thyroid disease, thyroid surgery, or preeclampsia/eclampsia were excluded. GDM was identified by ICD codes. The primary outcome was first diagnosis of thyroid disorders—hyperthyroidism, hypothyroidism, toxic/non-toxic goiter, thyroiditis (acute, subacute, Hashimoto’s), benign thyroid neoplasms, and thyroid cancer—after the index pregnancy. Propensity score matching (1:1) accounted for age, race, overweight/obesity, nicotine dependence, and alcohol abuse. Follow-up extended up to 20 years. Hazard ratios (HRs) were estimated using Cox models; cumulative incidence was compared with Kaplan–Meier analysis.ResultsAfter matching, GDM was associated with higher risks of hyperthyroidism (HR 1.60, 95% CI 1.30–1.99), hypothyroidism (HR 1.33, 95% CI 1.17–1.51), thyroiditis (HR 1.55, 95% CI 1.21–2.00), Hashimoto’s thyroiditis (HR 1.37, 95% CI 1.02–1.83), toxic goiter (HR 1.70, 95% CI 1.19–2.44), and non-toxic goiter (HR 1.26, 95% CI 1.10–1.45). No association was found for benign neoplasms or thyroid cancer. Risks were greater in women aged 35–45 years and those with BMI >25.ConclusionGDM is linked to increased long-term risk of multiple thyroid diseases, warranting extended thyroid monitoring in older and overweight/obese women.